Tissue Renin–Angiotensin System in Lacrimal Gland Fibrosis in a Murine Model of Chronic Graft-Versus-Host Disease. Issue 11 (November 2015) - Yaguchi, Saori; Ogawa, Yoko; Kawakita, Tetsuya; Shimmura, Shigeto; Tsubota, Kazuo
Abstract : Abstract: Chronic graft-versus-host disease (cGVHD) is a serious complication known to occur after allogeneic hematopoietic stem cell transplantation. Clinical manifestation includes inflammation and fibrosis. Many peripheral tissues are capable of generating the renin–angiotensin system (RAS) components, called the tissue RAS, and have various roles in tissue-specific physiological and pathological functions of inflammation and fibrosis. This article reviews evidence for the presence of the tissue RAS in the normal mouse lacrimal gland, the role of the tissue RAS in the fibrotic pathogenesis of the lacrimal gland in cGVHD model mice, and the effect of angiotensin II receptor blockers on preventing lacrimal gland fibrosis. B10.D2→BALB/c (H-2 d ) major histocompatibility complex-compatible, minor histocompatibility antigen-mismatched mice were used as a model of cGVHD, which reflects the clinical and pathological symptoms of human cGVHD. We also describe the localization of RAS components in the normal mouse lacrimal gland. In addition, we characterize the inflammatory and fibrotic changes of the lacrimal gland in cGVHD model mice, demonstrate that fibroblasts strongly express angiotensin II, angiotensin II type 1 receptor (AT1R), and angiotensin II type 2 receptor, and show that mRNA expression of angiotensinogen increased in the lacrimal gland of cGVHD model mice. Inhibitory experiments revealed that lacrimal gland fibrosis was suppressed in mice treated with an AT1R blocker, but not in mice treated with an angiotensin II type 2 receptor blocker. Hence, we conclude that the tissue RAS is involved in the fibrotic pathogenesis of the lacrimal gland and that AT1R blockers have a therapeutic effect on lacrimal gland fibrosis in cGVHD model mice.